Flexible sun-proof outdoor trampoline net fiber and preparation method thereof
By using activated carbon nanotubes and poly2,5-dihydroxy-1,4-phenylpyridinodiimidazole in the trampoline mesh fibers, combined with melt spinning, drafting and plasma treatment processes, the problem of performance degradation of trampoline mesh due to UV damage is solved, and the fibers are achieved with high mechanical properties and good anti-ultraviolet aging effect.
Patent Information
- Application Number
- CN202510159215.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing trampoline nets gradually deteriorate due to long-term exposure to ultraviolet light, resulting in a decrease in material viscosity and hardness, which in turn causes problems such as brittleness and cracking, affecting service life.
Using activated carbon nanotubes and poly2,5-dihydroxy-1,4-phenylpyridinodiimidazole and other materials, polymer fibers are prepared through melt spinning and secondary drafting, and plasma treatment is performed on the fiber surface, and finally the oxide fiber web is coated to improve the resistance to UV aging.
It significantly improves the mechanical properties of the fiber and the anti-ultraviolet aging effect, and extends the service life of the trampoline net.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite fibers, in particular to a flexible sun-resistant fiber for an outdoor trampoline net and a preparation method thereof. Background Art
[0002] As a popular fitness and entertainment project for minors, trampoline has been rapidly popularized in the streets and alleys because of its high playability, guaranteed safety, good exercise for children's coordination and cardiopulmonary function, and good improvement of children's cardiopulmonary function. Outdoor trampoline projects can also be seen everywhere, and the performance and life of trampoline nets will be significantly affected by long-term exposure to ultraviolet rays. Ultraviolet rays, especially UVA and UVB bands, can decompose the molecular bonds in polymer substances, causing their physical and chemical properties to gradually deteriorate, resulting in a decrease in material viscosity and hardness, and then causing brittleness, cracking and other problems, resulting in the loss of use value. In addition, ultraviolet rays will accelerate the decomposition and volatilization of additives in the material, further affecting the performance of the material. Therefore, the damage and aging of materials by ultraviolet rays are irreversible; therefore, a kind of ultraviolet-resistant fiber is prepared for outdoor trampoline nets to extend the service life. Summary of the invention
[0003] The object of the present invention is to provide a flexible sun-resistant fiber for outdoor trampoline net and a preparation method thereof, so as to solve the problems existing in the prior art.
[0004] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a flexible sun-resistant outdoor trampoline net fiber, comprising the following preparation steps: (1) Activated carbon nanotubes and acetone were mixed in a mass ratio of 1:3-7, stirred at 100-300 rpm for 5-15 min, ultrasonicated at 21 kHz for 5-15 min, and poly-2,5-dihydroxy-1,4-phenylene pyridine diimidazole (15-30 times the mass of activated carbon nanotubes) was added, the temperature was raised to 150-200°C, stirred at 80-160 rpm for 3-8 h, and then melt-spun, and secondary drawing was performed at 180°C, washed with deionized water for 5-10 times, dried at 70-90°C for 5-8 h, and finally treated with low-temperature plasma to obtain polymer fibers; (2) zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone and n-butanol are mixed, heated to 50-70°C, stirred at 150 rpm for 40-80 min, polyethylene oxide is added, and stirring is continued for 2-4 h. Under a vacuum degree of 50-150 mbar, one-half of the solvent in the solution is removed by rotary evaporation, and then dry spinning is performed at a spinning speed of 500-1000 m / min. Finally, the temperature is raised to 800-1300°C at a rate of 1-5°C / min, and the temperature is kept for 30-70 min to obtain oxide fibers. (3) At 120-160° C., a polyurethane mesh is coated on the polymer fiber, and then coated with a fiber mesh woven from oxide fibers to obtain a flexible, sun-resistant outdoor trampoline net fiber.
[0005] Furthermore, the preparation method of the activated carbon nanotubes in step (1) is as follows: multi-walled carbon nanotubes are subjected to high temperature treatment at a temperature of 300-500°C for a time of 150-250 min, then, in a 67wt% nitric acid aqueous solution of 30-70 times the mass of the multi-walled carbon nanotubes, ultrasonicated at 21kHz for 40-50 h, 72wt% sulfuric acid aqueous solution of 100-300 times the mass of the multi-walled carbon nanotubes is added and ultrasonicated for 3-8 h, then, the solid is taken out, ultrasonicated in a 20wt% hydrogen peroxide aqueous solution of 100-300 times the mass of the multi-walled carbon nanotubes for 2-5 h, while stirring at 100 rpm, 0°C deionized water of 500-700 times the mass of the multi-walled carbon nanotubes is added, and then filtered with a polytetrafluoroethylene microporous filter membrane with a pore size of 0.1 μm, washed with deionized water until the pH of the filtrate is 7-8, and dried at 70-90°C for 3-6 h.
[0006] Further, the preparation method of the poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole in step (1) is as follows: sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water are mixed in a mass ratio of 4-6:3:50-80, heated to 50-70°C under a nitrogen atmosphere, stirred at 50 rpm for 15 min, 12 wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution of 7 times the mass of sodium hydroxide is added, reacted for 15-30 min, 40 wt% phosphoric acid aqueous solution of 4-5 times the mass of sodium hydroxide is added, and the reaction is continued for 15-30 min. n, finally add 7wt% acetic acid aqueous solution with a mass of 0.9 times of sodium hydroxide, react for 30-50min, cool to room temperature, filter, take the solid, wash with deionized water for 3-8 times, and dry at 50°C for 5h to obtain intermediate A; mix intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder in a mass ratio of 3:8-12:2-2.5:0.01-0.1, stir at 20-50rpm under nitrogen atmosphere, heat to 100°C, keep warm for 45min, heat to 140°C, keep warm for 60min, and heat to 180°C, keep warm for 150min to obtain.
[0007] Furthermore, the process parameters of the melt spinning in step (1) are: temperature of 220-300° C. and speed of 200-600 m / min.
[0008] Furthermore, in the secondary stretching of step (1), the first stretching ratio is 1.3-1.8, and the second stretching ratio is 1.1-1.4.
[0009] Furthermore, the process parameters of the low-temperature plasma treatment in step (1) are as follows: the working gas is argon, the discharge power is 70-100 W, and the time is 15-50 s.
[0010] Furthermore, the molecular weight of the polyethylene oxide in step (2) is 1,000,000.
[0011] Furthermore, in step (2), the mass ratio of zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, n-butanol, and polyethylene oxide is 3:3~9:2~4:0.3:50:50:50~100.
[0012] Furthermore, the polyurethane mesh in step (3) has a density of 25 g / m 2 A024 polyurethane mesh.
[0013] Furthermore, the thickness of the fiber web in step (3) is 0.05-0.2 mm.
[0014] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention first performs activation treatment on multi-walled carbon nanotubes to remove impurities and introduce more carboxyl groups on the surface, thereby reducing the agglomeration of multi-walled carbon nanotubes, and partially separating single carbon nanotubes, which are then dispersed in a poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole matrix. The carbon nanotubes react with the amino groups at both ends of the matrix molecular chain through their carboxyl groups to generate amide groups, and assist in the stress transfer of the matrix. After melt spinning, polymer fibers are obtained. In this process, two stretching orientations are performed to further orient and crystallize the macromolecules in the matrix, and enhance the orderliness of the carbon nanotubes, thereby forming certain physical-mechanical properties and a stable structure, and improving the mechanical properties of the polymer fibers. Then, plasma treatment is carried out. On the one hand, the charged particles in the plasma can make the free single carbon nanotubes form small network aggregates and contact with other carbon nanotubes to form conductive paths and enhance the overall shielding performance. The half-wavelength of ultraviolet rays is close to the electric dipole moment of well-dispersed carbon nanotubes. At the same time, carbon nanotubes can also hinder the development of matrix aging through their own chain segments, thereby greatly improving the anti-ultraviolet aging effect of the fiber; on the other hand, plasma etches on the fiber, increasing the polar groups on its surface, thereby enhancing the bonding force between the fiber and the adhesive, and finally by coating the fiber web, the mechanical properties and anti-ultraviolet aging effect of the fiber are greatly improved.
[0015] The fibers in the fiber mesh are made of silicon oxide as a matrix, and the matrix is made to achieve anti-ultraviolet properties by adding zinc powder, and the mechanical properties of the matrix are enhanced by adding a zirconium source. After co-spinning and then high-temperature treatment, the fiber ceramic phase transition is achieved. Amorphous silicon oxide increases the activation energy of grain growth, inhibits grain growth, and improves the mechanical properties of the fiber. Amorphous silicon oxide coats nanoscale polycrystalline zirconium oxide particles and hexagonal zinc oxide to enhance the stability of zinc oxide at high temperatures, thereby enhancing the anti-ultraviolet aging properties of the matrix. Silicon oxide is interconnected through its tetrahedrons to form a network structure, and under external stress, the continuous structure of the tetrahedrons interconnected will undergo elastic deformation due to changes in the angle of the long silicon-oxygen-silicon bond. Zirconium oxide and zinc oxide particles can act as pinning to limit the migration of the silicon oxide matrix and provide stiffness for the fiber as a whole, thereby synergistically achieving the effect of high strength and high toughness of the matrix fiber. DETAILED DESCRIPTION
[0016] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0017] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the flexible sun-resistant outdoor trampoline net fiber prepared in the following examples are as follows: Mechanical properties: The same size of the embodiment and the comparative example were taken to test the strength and resilience of the fiber according to GB / T14337 and BS1902 respectively.
[0018] UV resistance: The same size of the embodiment and the comparative example were placed in a UV aging test box, irradiated with UV light for 48 hours, and then taken out for strength test.
[0019] Example 1: (1) The multi-walled carbon nanotubes were subjected to high temperature treatment at 300°C for 150 min, then ultrasonicated at 21 kHz for 40 h in a 67 wt% nitric acid aqueous solution with a mass of 30 times that of the multi-walled carbon nanotubes, and ultrasonicated for 3 h in a 72 wt% sulfuric acid aqueous solution with a mass of 100 times that of the multi-walled carbon nanotubes. Then, the solid was taken out and ultrasonicated for 2 h in a 20 wt% hydrogen peroxide aqueous solution with a mass of 100 times that of the multi-walled carbon nanotubes, while stirring at 100 rpm, 0°C deionized water with a mass of 500 times that of the multi-walled carbon nanotubes was added, and then the solid was treated with a polytetrafluoroethylene with a pore size of 0.1 μm. The mixture was filtered through an olefin microporous filter membrane, washed with deionized water until the pH value of the filtrate was 7, and dried at 70°C for 3 hours to obtain activated carbon nanotubes; sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water were mixed in a mass ratio of 4:3:50, heated to 50°C under a nitrogen atmosphere, stirred at 50 rpm for 15 minutes, 12 wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution (7 times the mass of sodium hydroxide) was added, reacted for 15 minutes, 40 wt% phosphoric acid aqueous solution (4 times the mass of sodium hydroxide) was added, the reaction was continued for 15 minutes, and finally 7 wt% acetic acid aqueous solution (0.9 times the mass of sodium hydroxide) was added. The solution was reacted for 30 minutes, cooled to room temperature, filtered, and the solid was taken, washed with deionized water for 3 times, and dried at 50°C for 5 hours to obtain intermediate A; intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder were mixed in a mass ratio of 3:8:2:0.01, stirred at 20 rpm under a nitrogen atmosphere, and heated to 100°C and kept warm for 45 minutes, heated to 140°C and kept warm for 60 minutes, and 180°C and kept warm for 150 minutes to obtain poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole; activated carbon nanotubes and acetone were mixed in a mass ratio of 1:3, stirred at 100 rpm for 5 minutes , 21kHz ultrasound for 5 minutes, add poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole with a mass of 15 times that of activated carbon nanotubes, heat to 150°C, stir at 80rpm for 3h, and then melt-spin at a temperature of 220°C and a speed of 200m / min, and perform secondary drawing at 180°C, the first drawing ratio is 1.3, the second drawing ratio is 1.1, wash with deionized water 5 times, dry at 70°C for 5h, and finally treat with low-temperature plasma, the process parameters are as follows: working gas is argon, discharge power is 70W, time is 15s, and polymer fibers are obtained; (2) zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, and n-butanol were mixed, heated to 50°C, stirred at 150 rpm for 40 min, polyethylene oxide with a molecular weight of 1,000,000 was added, and stirring was continued for 2 h. Under a vacuum degree of 50 mbar, half of the solvent in the solution was removed by rotary evaporation, and then dry spinning was performed at a spinning speed of 500 m / min. Finally, the temperature was raised to 800°C at a rate of 1°C / min and kept warm for 30 min to obtain oxide fibers; the mass ratio of zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, n-butanol, and polyethylene oxide with a molecular weight of 1,000,000 was 3:3:2:0.3:50:50:50; (3) At 120°C, a density of 25 g / m 2 The A024 type polyurethane mesh film is coated on the polymer fiber, and then coated with a fiber mesh woven from oxide fibers with a thickness of 0.05mm to obtain a flexible sun-resistant outdoor trampoline net fiber.
[0020] Example 2: (1) The multi-walled carbon nanotubes were subjected to high temperature treatment at 400°C for 200 min, then ultrasonicated at 21 kHz for 45 h in a 67 wt% nitric acid aqueous solution with a mass of 50 times that of the multi-walled carbon nanotubes, and then ultrasonicated for 5 h in a 72 wt% sulfuric acid aqueous solution with a mass of 200 times that of the multi-walled carbon nanotubes. Then, the solid was taken out and ultrasonicated for 3.5 h in a 20 wt% hydrogen peroxide aqueous solution with a mass of 200 times that of the multi-walled carbon nanotubes, while stirring at 100 rpm, 0°C deionized water with a mass of 600 times that of the multi-walled carbon nanotubes was added, and then a polytetrafluoroethylene with a pore size of 0.1 μm was used. The microporous filter membrane was filtered, washed with deionized water until the pH value of the filtrate was 7.5, and dried at 80°C for 4.5 hours to obtain activated carbon nanotubes; sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water were mixed in a mass ratio of 5:3:65, heated to 60°C under a nitrogen atmosphere, stirred at 50 rpm for 15 minutes, 12 wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution (7 times the mass of sodium hydroxide) was added, reacted for 23 minutes, 40 wt% phosphoric acid aqueous solution (4.5 times the mass of sodium hydroxide) was added, the reaction was continued for 23 minutes, and finally 7 wt% acetic acid (0.9 times the mass of sodium hydroxide) was added. The aqueous solution was reacted for 40 minutes, cooled to room temperature, filtered, and the solid was taken, washed with deionized water for 6 times, and dried at 50°C for 5 hours to obtain intermediate A; intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder were mixed in a mass ratio of 3:10:2.2:0.06, stirred at 40 rpm under a nitrogen atmosphere, and heated to 100°C and kept warm for 45 minutes, heated to 140°C and kept warm for 60 minutes, and 180°C and kept warm for 150 minutes to obtain poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole; activated carbon nanotubes and acetone were mixed in a mass ratio of 1:5, stirred at 500 rpm for 10 minutes n, 21kHz ultrasound for 10min, add poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole with a mass of 23 times that of activated carbon nanotubes, heat to 180℃, stir at 120rpm for 5h, and then melt-spin at a temperature of 260℃ and a speed of 400m / min, and perform secondary drawing at 180℃, the first drawing ratio is 1.5, and the second drawing ratio is 1.2, wash with deionized water 8 times, dry at 80℃ for 7h, and finally treat with low-temperature plasma, the process parameters are as follows: working gas is argon, discharge power is 80W, time is 36s, and polymer fiber is obtained; (2) zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, and n-butanol were mixed, heated to 60°C, stirred at 150 rpm for 60 min, polyethylene oxide with a molecular weight of 1,000,000 was added, and stirring was continued for 3 h. Under a vacuum degree of 100 mbar, half of the solvent in the solution was removed by rotary evaporation, and then dry spinning was performed at a spinning speed of 750 m / min. Finally, the temperature was raised to 1000°C at a rate of 3°C / min and kept warm for 50 min to obtain oxide fibers. The mass ratio of zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, n-butanol, and polyethylene oxide with a molecular weight of 1,000,000 was 3:6:3:0.3:50:50:70. (3) At 140°C, a density of 25 g / m 2 The A024 type polyurethane mesh film is coated on the polymer fiber, and then coated with a fiber mesh woven from oxide fibers with a thickness of 0.12mm to obtain a flexible sun-resistant outdoor trampoline net fiber.
[0021] Example 3: (1) The multi-walled carbon nanotubes were subjected to high temperature treatment at 500°C for 250 min, then ultrasonicated at 21 kHz for 50 h in a 67 wt % nitric acid aqueous solution (70 times the mass of the multi-walled carbon nanotubes), and ultrasonicated for 8 h after adding a 72 wt % sulfuric acid aqueous solution (300 times the mass of the multi-walled carbon nanotubes). Subsequently, the solid was taken out and ultrasonicated for 5 h in a 20 wt % hydrogen peroxide aqueous solution (300 times the mass of the multi-walled carbon nanotubes), while stirring at 100 rpm, 0°C deionized water (700 times the mass of the multi-walled carbon nanotubes) was added, and then the solid was filtered with a polytetrafluoroethylene micro-tube having a pore size of 0.1 μm. The mixture was filtered through a porous membrane, washed with deionized water until the pH value of the filtrate was 8, and dried at 90°C for 6h to obtain activated carbon nanotubes; sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water were mixed in a mass ratio of 6:3:80, heated to 70°C under a nitrogen atmosphere, stirred at 50rpm for 15min, 12wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution (7 times the mass of sodium hydroxide) was added, reacted for 30min, 40wt% phosphoric acid aqueous solution (5 times the mass of sodium hydroxide) was added, the reaction was continued for 30min, and finally 7wt% acetic acid aqueous solution (0.9 times the mass of sodium hydroxide) was added, and the reaction was continued for 15min. The mixture was stirred at 50 rpm under nitrogen atmosphere, and heated to 100°C for 45 min, heated to 140°C for 60 min, and heated to 180°C for 150 min to obtain poly-2,5-dihydroxy-1,4-phenylenepyridine diimidazole; activated carbon nanotubes and acetone were mixed at a mass ratio of 1:7, stirred at 300 rpm for 15 min, and heated to 140°C for 60 min, and heated to 180°C for 150 min to obtain poly-2,5-dihydroxy-1,4-phenylenepyridine diimidazole; activated carbon nanotubes and acetone were mixed at a mass ratio of 1:7, and stirred at 300 rpm for 15 min. kHz ultrasound for 15 minutes, add poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole with a mass of 30 times that of activated carbon nanotubes, heat to 200°C, stir at 160rpm for 8 hours, and then melt-spin at a temperature of 300°C and a speed of 600m / min, and perform secondary drawing at 180°C, the first drawing ratio is 1.8, and the second drawing ratio is 1.4, wash with deionized water 10 times, dry at 90°C for 8 hours, and finally treat with low-temperature plasma, the process parameters of which are as follows: working gas is argon, discharge power is 100W, and time is 50s, to obtain polymer fibers; (2) zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, and n-butanol were mixed, heated to 70°C, stirred at 150 rpm for 80 min, polyethylene oxide with a molecular weight of 1,000,000 was added, and stirring was continued for 4 h. Under a vacuum degree of 150 mbar, half of the solvent in the solution was removed by rotary evaporation, and then dry spinning was performed at a spinning speed of 1,000 m / min. Finally, the temperature was raised to 1,300°C at a rate of 5°C / min and kept warm for 70 min to obtain oxide fibers. The mass ratio of zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, n-butanol, and polyethylene oxide with a molecular weight of 1,000,000 was 3:9:4:0.3:50:50:100. (3) At 160°C, a density of 25 g / m 2 The A024 type polyurethane mesh film is coated on the polymer fiber, and then coated with a fiber mesh woven from oxide fibers with a thickness of 0.2mm to obtain a flexible sun-resistant outdoor trampoline net fiber.
[0022] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water are mixed in a mass ratio of 5:3:65, heated to 60°C under a nitrogen atmosphere, stirred at 50 rpm for 15 min, 12 wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution of 7 times the mass of sodium hydroxide is added, reacted for 23 min, 40 wt% phosphoric acid aqueous solution of 4.5 times the mass of sodium hydroxide is added, the reaction is continued for 23 min, and finally 7 wt% acetic acid aqueous solution of 0.9 times the mass of sodium hydroxide is added, reacted for 40 min, cooled to room temperature, filtered, solids are taken, washed with deionized water 6 times, and dried at 50°C for 5 h to obtain intermediate A; intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder are mixed in a mass ratio of 3:10:2.2:0.06, stirred at 40 rpm under a nitrogen atmosphere, and heated to 100°C. , keep warm for 45 minutes, heat to 140℃, keep warm for 60 minutes, 180℃, keep warm for 150 minutes to obtain poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole; multi-walled carbon nanotubes and acetone were mixed in a mass ratio of 1:5, stirred at 500rpm for 10 minutes, ultrasonicated at 21kHz for 10 minutes, poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole (23 times the mass of multi-walled carbon nanotubes) was added, heated to 180℃, 1 The mixture was stirred at 20 rpm for 5 h, and then melt-spinning was carried out at a temperature of 260 ° C and a speed of 400 m / min. The fiber was stretched twice at 180 ° C, with the first stretching ratio being 1.5 and the second stretching ratio being 1.2. The fiber was washed with deionized water for 8 times, dried at 80 ° C for 7 h, and finally treated with low-temperature plasma with the process parameters as follows: the working gas was argon, the discharge power was 80 W, and the time was 36 s to obtain polymer fibers. The remaining steps were the same as those in Example 2.
[0023] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: sodium hydroxide, 2,5-dihydroxyterephthalic acid and deionized water are mixed in a mass ratio of 5:3:65, heated to 60°C under a nitrogen atmosphere, stirred at 50 rpm for 15 min, 12 wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution of 7 times the mass of sodium hydroxide is added, reacted for 23 min, 40 wt% phosphoric acid aqueous solution of 4.5 times the mass of sodium hydroxide is added, the reaction is continued for 23 min, and finally 7 wt% acetic acid aqueous solution of 0.9 times the mass of sodium hydroxide is added, reacted for 40 min, cooled to room temperature, filtered, solids are taken, washed with deionized water 6 times, and dried at 50°C for 5 h to obtain intermediate A; intermediate A, polyphosphoric acid, phosphorus pentoxide and tin powder are mixed in a mass ratio of 3:10:2.2: 0.06, stirred at 40 rpm under nitrogen atmosphere, and heated to 100° C. and kept warm for 45 min, heated to 140° C. and kept warm for 60 min, and kept warm at 180° C. for 150 min to obtain poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole; the poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole was heated to 180° C. and stirred at 120 rpm for 5 h, and then melt-spun at a temperature of 260° C. and a speed of 400 m / min, and stretched twice at 180° C., with the first stretching ratio of 1.5 and the second stretching ratio of 1.2, washed with deionized water 8 times, dried at 80° C. for 7 h, and finally treated with low-temperature plasma, with process parameters as follows: working gas is argon, discharge power is 80 W, and time is 36 s to obtain polymer fiber; the remaining steps are the same as those in Example 2.
[0024] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (1) is different, and step (1) is changed to: the multi-walled carbon nanotubes are subjected to high temperature treatment at a temperature of 400°C for 200 min, then, in a 67wt% nitric acid aqueous solution with a mass of 50 times that of the multi-walled carbon nanotubes, ultrasonicated at 21kHz for 45h, 72wt% sulfuric acid aqueous solution with a mass of 200 times that of the multi-walled carbon nanotubes is added and ultrasonicated for 5h, then, the solid is taken out and ultrasonicated in a 20wt% hydrogen peroxide aqueous solution with a mass of 200 times that of the multi-walled carbon nanotubes for 3.5h, while stirring at 100rpm, 60wt% of the multi-walled carbon nanotubes are added. 0 times of 0℃ deionized water, and then filtered with a polytetrafluoroethylene microporous filter membrane with a pore size of 0.1μm, washed with deionized water until the pH of the filtrate is 7.5, and dried at 80℃ for 4.5h to obtain activated carbon nanotubes; sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water were mixed in a mass ratio of 5:3:65, heated to 60℃ under a nitrogen atmosphere, stirred at 50rpm for 15min, 12wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution with a mass of 7 times of sodium hydroxide was added, reacted for 23min, 40wt% phosphoric acid aqueous solution with a mass of 4.5 times of sodium hydroxide was added, and the reaction was continued. The mixture was stirred for 23 minutes, and finally a 7wt% acetic acid aqueous solution with a mass of 0.9 times that of sodium hydroxide was added, and the mixture was reacted for 40 minutes. The mixture was cooled to room temperature, filtered, and the solid was taken out. The solid was washed with deionized water for 6 times and dried at 50°C for 5 hours to obtain intermediate A. Intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder were mixed in a mass ratio of 3:10:2.2:0.06, stirred at 40 rpm under a nitrogen atmosphere, and heated to 100°C and kept warm for 45 minutes, then heated to 140°C and kept warm for 60 minutes, and then heated to 180°C and kept warm for 150 minutes to obtain poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole. The activated carbon was added Nanotubes and acetone were mixed in a mass ratio of 1:5, stirred at 500 rpm for 10 min, and ultrasonicated at 21 kHz for 10 min. Poly (2,5-dihydroxy-1,4-phenylene pyridine diimidazole) with a mass of 23 times that of activated carbon nanotubes was added. The temperature was raised to 180° C. and stirred at 120 rpm for 5 h. Melt spinning was then carried out at a temperature of 260° C. and a speed of 400 m / min. The mixture was washed with deionized water for 8 times, dried at 80° C. for 7 h, and finally treated with low-temperature plasma. The process parameters were as follows: the working gas was argon, the discharge power was 80 W, and the time was 36 s. Polymer fibers were obtained. The remaining steps were the same as those in Example 2.
[0025] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (1) is different, and step (1) is changed to: the multi-walled carbon nanotubes are subjected to high temperature treatment at a temperature of 400°C for 200 min, then, in a 67wt% nitric acid aqueous solution with a mass of 50 times that of the multi-walled carbon nanotubes, ultrasonicated at 21kHz for 45h, 72wt% sulfuric acid aqueous solution with a mass of 200 times that of the multi-walled carbon nanotubes is added and ultrasonicated for 5h, then, the solid is taken out and ultrasonicated in a 20wt% hydrogen peroxide aqueous solution with a mass of 200 times that of the multi-walled carbon nanotubes for 3.5h, while stirring at 100rpm, 6wt% of the multi-walled carbon nanotubes are added. 00 times of 0℃ deionized water, and then filtered with a polytetrafluoroethylene microporous filter membrane with a pore size of 0.1μm, washed with deionized water until the pH of the filtrate is 7.5, and dried at 80℃ for 4.5h to obtain activated carbon nanotubes; sodium hydroxide, 2,5-dihydroxyterephthalic acid, and deionized water were mixed in a mass ratio of 5:3:65, heated to 60℃ under a nitrogen atmosphere, stirred at 50rpm for 15min, 12wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution with a mass of 7 times of sodium hydroxide was added, reacted for 23min, 40wt% phosphoric acid aqueous solution with a mass of 4.5 times of sodium hydroxide was added, and then The reaction was continued for 23 minutes, and finally a 7wt% acetic acid aqueous solution with a mass of 0.9 times that of sodium hydroxide was added, and the reaction was continued for 40 minutes. The mixture was cooled to room temperature, filtered, and the solid was taken out, washed with deionized water for 6 times, and dried at 50°C for 5 hours to obtain intermediate A. Intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder were mixed in a mass ratio of 3:10:2.2:0.06, stirred at 40 rpm under a nitrogen atmosphere, and heated to 100°C and kept warm for 45 minutes, then heated to 140°C and kept warm for 60 minutes, and then heated to 180°C and kept warm for 150 minutes to obtain poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole. Activated carbon nanotubes and acetone were mixed in a mass ratio of 1:5, stirred at 500 rpm for 10 min, and ultrasonicated at 21 kHz for 10 min. Poly (2,5-dihydroxy-1,4-phenylene pyridine diimidazole) with a mass of 23 times that of the activated carbon nanotubes was added. The temperature was raised to 180°C, stirred at 120 rpm for 5 h, and then melt-spinning was carried out at a temperature of 260°C and a speed of 400 m / min. The fiber was stretched twice at 180°C, with the first stretching ratio being 1.5 and the second stretching ratio being 1.2. The fiber was washed 8 times with deionized water and dried at 80°C for 7 h to obtain polymer fibers. The remaining steps were the same as those in Example 2.
[0026] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (2) is different. Step (2) is changed to: zirconium oxychloride octahydrate, tetraethyl orthosilicate, yttrium nitrate hexahydrate, acetylacetone and n-butanol are mixed, the temperature is raised to 60°C, and stirred at 150rpm for 60min, polyethylene oxide with a molecular weight of 1000000 is added, and stirring is continued for 3h. Under a vacuum degree of 100mbar, half of the solvent in the solution is removed by rotary evaporation, and then dry spinning is carried out at a spinning speed of 750m / min. Finally, the temperature is raised to 1000°C at 3°C / min and kept warm for 50min to obtain oxide fibers. The mass ratio of zirconium oxychloride octahydrate, tetraethyl orthosilicate, yttrium nitrate hexahydrate, acetylacetone, n-butanol and polyethylene oxide with a molecular weight of 1000000 is 3:6:0.3:50:50:70. The remaining steps are the same as those in Example 2.
[0027] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (2) is different. Step (2) is changed to: tetraethyl orthosilicate, zinc powder, acetylacetone and n-butanol are mixed, the temperature is raised to 60°C, and the mixture is stirred at 150 rpm for 60 min. Polyethylene oxide with a molecular weight of 1000000 is added, and the stirring is continued for 3 h. Under a vacuum degree of 100 mbar, half of the solvent in the solution is removed by rotary evaporation, and then dry spinning is carried out at a spinning speed of 750 m / min. Finally, the temperature is raised to 1000°C at a rate of 3°C / min and the mixture is kept warm for 50 min to obtain oxide fibers. The mass ratio of tetraethyl orthosilicate, zinc powder, acetylacetone, n-butanol and polyethylene oxide with a molecular weight of 1000000 is 6:3:50:50:70. The remaining steps are the same as those in Example 2.
[0028] Effect example Table 1 below shows the performance analysis results of the flexible sun-resistant outdoor trampoline net fibers of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.
[0029] Table 1
[0030] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention first activates the multi-walled carbon nanotubes to remove impurities and introduce more carboxyl groups on the surface, thereby reducing the agglomeration of the multi-walled carbon nanotubes, and partially separates single carbon nanotubes, which are then dispersed in a poly-2,5-dihydroxy-1,4-phenylene pyridine diimidazole matrix to assist the matrix stress transfer, and obtain polymer fibers through melt spinning. In this process, two stretching orientations are performed to further orient and crystallize the macromolecules in the matrix, and enhance the orderliness of the carbon nanotubes, thereby improving the mechanical properties of the polymer fibers. Subsequently, plasma treatment is performed. On the one hand, the charged particles in the plasma can cause the free single carbon nanotubes to form small mesh aggregates, and contact with other carbon nanotubes to form a conductive path and enhance the overall ultraviolet shielding performance. On the other hand, the plasma plays an etching role on the fiber, increasing the polar groups on its surface. The fiber mesh is coated with silicon oxide as a matrix, and the matrix is made to achieve anti-ultraviolet performance by adding zinc powder, and the mechanical properties of the matrix are enhanced by adding a zirconium source. After co-spinning and high-temperature treatment, the fiber ceramic phase is transformed, and amorphous silicon oxide is coated with nano-scale polycrystalline zirconium oxide particles and hexagonal zinc oxide to enhance the stability of zinc oxide at high temperatures, thereby enhancing the anti-ultraviolet aging performance of the matrix. Silicon oxide is interconnected through its tetrahedrons to form a network structure, and under external stress, the continuous structure of the tetrahedrons interconnected will undergo elastic deformation due to the change of the long bond angle of silicon oxygen silicon, and the zirconium oxide and zinc oxide particles can be used as pinning to limit the migration of the silicon oxide matrix, provide stiffness for the fiber as a whole, thereby synergistically achieving the effect of high strength and high toughness of the matrix fiber.
[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing a flexible sun-resistant outdoor trampoline net fiber, characterized in that: The method comprises the following preparation steps: (1) The multi-walled carbon nanotubes were subjected to high temperature treatment at a temperature of 300-500°C for 150-250 min, and then ultrasonicated at 21 kHz for 40-50 h in a 67 wt % nitric acid aqueous solution with a mass of 30-70 times the mass of the multi-walled carbon nanotubes, and then ultrasonicated for 3-8 h in a 72 wt % sulfuric acid aqueous solution with a mass of 100-300 times the mass of the multi-walled carbon nanotubes. Subsequently, the solid was taken out and ultrasonicated for 2-5 h in a 20 wt % hydrogen peroxide aqueous solution with a mass of 100-300 times the mass of the multi-walled carbon nanotubes, and deionized water at 0°C with a mass of 500-700 times the mass of the multi-walled carbon nanotubes was added while stirring at 100 rpm, and then the solid was extracted with a polytetrafluoroethylene microporous filter membrane with a pore size of 0.1 μm. Filter, wash with deionized water until the pH value of the filtrate is 7-8, and dry at 70-90°C for 3-6 hours to obtain activated carbon nanotubes; mix the activated carbon nanotubes and acetone in a mass ratio of 1:3-7, stir at 100-300rpm for 5-15min, and ultrasonicate at 21kHz for 5-15min, add poly-2,5-dihydroxy-1,4-phenylene pyridine diimidazole with a mass of 15-30 times of the activated carbon nanotubes, heat to 150-200°C, stir at 80-160rpm for 3-8h, and then melt-spin, and perform secondary drawing at 180°C, wash with deionized water for 5-10 times, and dry at 70-90°C for 5-8h, and finally treat with low-temperature plasma to obtain polymer fibers; (2) zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone and n-butanol are mixed, heated to 50-70°C, stirred at 150 rpm for 40-80 min, polyethylene oxide is added, and stirring is continued for 2-4 h. Under a vacuum degree of 50-150 mbar, one-half of the solvent in the solution is removed by rotary evaporation, and then dry spinning is performed at a spinning speed of 500-1000 m / min. Finally, the temperature is raised to 800-1300°C at a rate of 1-5°C / min, and the temperature is kept for 30-70 min to obtain oxide fibers. (3) At 120-160° C., a polyurethane mesh is coated on the polymer fiber, and then coated with a fiber mesh woven from oxide fibers to obtain a flexible, sun-resistant outdoor trampoline net fiber.
2. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The preparation method of the poly 2,5-dihydroxy-1,4-phenylene pyridine diimidazole in step (1) is as follows: sodium hydroxide, 2,5-dihydroxyterephthalic acid and deionized water are mixed in a mass ratio of 4-6:3:50-80, heated to 50-70°C under a nitrogen atmosphere, stirred at 50 rpm for 15 minutes, 12 wt% 2,3,5,6-tetraaminopyridine hydrochloride aqueous solution of 7 times the mass of sodium hydroxide is added, reacted for 15-30 minutes, 40 wt% phosphoric acid aqueous solution of 4-5 times the mass of sodium hydroxide is added, and the reaction is continued for 15-30 minutes. Finally, add 7wt% acetic acid aqueous solution with a mass of 0.9 times that of sodium hydroxide, react for 30-50min, cool to room temperature, filter, take the solid, wash with deionized water 3-8 times, and dry at 50°C for 5h to obtain intermediate A; mix intermediate A, polyphosphoric acid, phosphorus pentoxide, and tin powder in a mass ratio of 3:8-12:2-2.5:0.01-0.1, stir at 20-50rpm under nitrogen atmosphere, heat to 100°C, keep warm for 45min, heat to 140°C, keep warm for 60min, and heat to 180°C, keep warm for 150min to obtain.
3. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The process parameters of the melt spinning in step (1) are: temperature of 220-300° C. and speed of 200-600 m / min.
4. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: In the secondary drawing in step (1), the first drawing ratio is 1.3-1.8, and the second drawing ratio is 1.1-1.
4.
5. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The process parameters of the low-temperature plasma treatment in step (1) are as follows: the working gas is argon, the discharge power is 70-100 W, and the time is 15-50 s.
6. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The molecular weight of the polyethylene oxide in step (2) is 1,000,000.
7. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The mass ratio of zirconium oxychloride octahydrate, tetraethyl orthosilicate, zinc powder, yttrium nitrate hexahydrate, acetylacetone, n-butanol and polyethylene oxide in step (2) is 3:3-9:2-4:0.3:50:50:50-100.
8. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The polyurethane mesh in step (3) has a density of 25 g / m 2 A024 polyurethane mesh.
9. The method for preparing a flexible sun-resistant fiber for outdoor trampoline net according to claim 1, characterized in that: The thickness of the fiber web in step (3) is 0.05-0.2 mm.